1976
DOI: 10.2134/agronj1976.00021962006800050013x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification Inhibitor with Fall‐applied vs. Split Nitrogen Applications for Winter Wheat1

Abstract: Since numerous small grain producers desire to make fall application of efficient levels of N for maximum yields, studies are needed to determine the efficiency of fall‐applied N (with and without an inhibitor) vs. split N applications. Field studies were conducted at two locations each year over a 3‐year period with the objective of evaluating the response of wheat (Triticum aestivum L.) to N rates, time of application, and effect of a nitrification inhibitor on soils of different characteristics (Typic Haplu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…In such cases, the strategy was to hold ammonium in the soil thereby retarding its oxidation to nitrate. The use of nitrification inhibitors may offer an alternative to splitting N applications (Boswell et al, 1976) in order to improve the efficiency of applied N.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, the strategy was to hold ammonium in the soil thereby retarding its oxidation to nitrate. The use of nitrification inhibitors may offer an alternative to splitting N applications (Boswell et al, 1976) in order to improve the efficiency of applied N.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison between treatments with and without CMP indicated that inclusion of CMP with treatments had no significant effects on improving the cotton yields at any rate of application studied. Previous studies have revealed that the effects of nitrification on crop yields depended on soil, climatic conditions as well as management practices (Boswell et al, 1976;Rao, 1996).…”
Section: Effect Of Nitrification Inhibitor On Soil No 3 ϫ -N Levelsmentioning
confidence: 99%
“…Even though a dry winter followed the second season, adequate summer rainfall allowed good maize yields and utilization of N fertilizer by the maize. Substantial wheat yields with no or limited N application have been obtained in Coastal Plain soils in certain situations, indicating significant N carryover from one crop to the next (Camberato, 1990, unpublished data;Boswell et al, 1976;Gravelle et al, 1988). More extensive experimentation as well as water use modeling should be employed to determine the potential for N carryover from one crop to the next in the Coastal Plain environment.…”
Section: Anthesis Harvest Nitrogenmentioning
confidence: 99%